Acidic pretreatment of a copper-silver ore and its beneficial effect on cyanide leaching - Portilla, Renzo E. (2020)
The presence of copper in ores containing noble metals results in a high consumption of cyanide during leaching, which is undesirable from economic and environmental standpoints. Substantial previous work targets copper-gold ores, but the present study focuses on a copper-silver ore, which will be leached following acidic pretreatment (sulfuric acid at pH 1) to assess the effect of copper in cyanide consumption and silver extraction. The ore is mainly composed of hematite/goethite and silicates, with copper (0.15%) and silver (250 ppm) mostly present as sulfides and sulfosalts. The acidic pretreatment dissolves 18% of the copper content, which in turn decreases the cyanide consumption from 7 to 3 kg NaCN/ton in a five-hour leaching. Mineralogical changes, followed by polarization microscopy, are only minimal and restricted to iron oxides, while silicates and sulfides remain unchanged. However, X-ray photoelectron spectroscopy shows that surface copper oxides and calcium are removed during acidic pretreatment, without removing silver or copper sulfides. While no significant increase in silver extraction is observed after pretreatment, silver extraction takes place at a significantly faster rate, which demonstrates that copper decreases the kinetics of leaching and is responsible for a high consumption of cyanide during leaching. This work highlights the need for understanding the solubility of copper compounds to design strategies aimed at improving the efficiency of cyanide leaching in copper-silver ores.